Self-treatment of malaria in rural communities, Butajira, southern Ethiopia - Deressa Wakgari; Ali A.; Enqusellassie F. (The World Health Organization, 2003)
OBJECTIVES: To quantify the use of self-treatment and to determine the actions taken to manage malaria illness. METHODS: A cross-sectional study was undertaken in six peasant associations in Butajira district, southern Ethiopia, between January and September 1999. Simple random sampling was used to select a sample of 630 households with malaria cases within the last six months. FINDINGS: Overall, 616 (>97%) of the study households acted to manage malaria, including the use of antimalarial drugs at home (112, 17.8%), visiting health services after taking medication at home (294, 46.7%), and taking malaria patients to health care facilities without home treatment (210, 33.3%). Although 406 (64.5%) of the households initiated treatment at home, the use of modern drugs was higher (579, 92%) than that of traditional medicine (51, 8%). Modern drugs used included chloroquine (457, 73.5%) and sulfadoxine-pyrimethamine (377, 60.6%). Malaria control programmes were the main sources of antimalarials. In most cases of malaria, treatment was started (322, 52.3%) or health services visited (175, 34.7%) within two days of the onset of symptoms. Cases of malaria in the lowland areas started treatment and visited health services longer after the onset of malaria than those in the midland areas (adjusted odds ratio, 0.44; 95% confidence interval (CI), 0.30-0.64; and adjusted odds ratio, 0.37; 95% CI, 0.25-0.56, respectively). Similarly, those further than one hour's walk from the nearest health care facility initiated treatment later than those with less than one hour's walk (adjusted odds ratio, 0.62; 95% CI 0.43-0.87). This might be because of inaccessibility to antimalarial drugs and distant health care facilities in the lowland areas; however, statistically insignificant associations were found for sex, age, and religion. CONCLUSION: Self-treatment at home is the major action taken to manage malaria. Efforts should be made to improve the availability of effective antimalarials to communities in rural areas with malaria, particularly through the use of community health workers, mother coordinators, drug sellers, and shop owners.